Uso de biomarcadores na vigilância em hanseníase : análise- têmporo-espacial - Camargo, Núbia Cássia (2011)
The combination of epidemiological, molecular and immunological tools and geographical information system (GIS) can elucidate not only clusters of cases of leprosy, as well as groups at higher risk of developing the disease among household contacts. This study characterized the leprosy in Uberlândia / MG, Brazil, from 2001 to 2008, using epidemiological indicators and GIS for surveillance of infection with M. leprae in household contacts and patients seropositive to ELISA anti-PGL-1 and / or PCR to detect the M. leprae DNA in nasal and buccal swabs. A number of 683 leprosy cases were georeferenced and 262 positive contacts for these exams. Reported cases was observed in the operational classification that more MB was the predominant (67.2%), the clinical form D was the most prevalent (47.9%), the disability grade 2 at diagnosis was 11.1 %. Men accounted for 58.7% of new cases, a rate male/female 1.4, the predominant age group was 35 to 59 years (50.5%). As for the epidemiological indicators, the annual detection rate new cases ranged from 11 to 20 cases remained as highly endemic, with 13.3 cases per 100,000, showing a decline of 35% in detecting new cases at the end of 2008 (p <0.05). The annual detection rate of new cases in children under 15 years ranged from 0 to 2.2 cases to 1.4 cases per 100,000 inhabitants in 2008, maintaining endemic average parameter that indicates recent and active infection in the city. The coefficient ratio new cases with disability grade 2 at diagnosis ranged from 4.2% to 24.3%, with a proportion of 12.7% in 2008, with a high parameter of disabled, indicating a late diagnosis and the evaluation and improvement or record of disability. The detection rates of new cases in 2001 were higher in SSS and SSO, and in 2008, remained high in the SSS and moved to the SSN SSO, coinciding with the expansion of industrialization of the city center, where there was an increase in population density. Clusters hyperendemic leprosy were identified in the SSC and the SSS and these both districts that received the graduates of the leprosy colonies in the 60 and 70 and where it still remains a big factor stigma surrounding the disease by the presence of sequelae. The surveillance of infection with M. leprae in household contacts found that 15.7% of infected and healthy carriers of the bacillus, distributed in 7.2% seropositive to ELISA anti-PGL-I, 5% positive buccal swab and 3.8% in the nasal swab for detection the M. leprae DNA. The highest positivity was found in contacts of index cases MB. As for the ELISA, the seropositivity was higher in women (64%). It was shown in a cluster of infected contacts and SSS or healthy carriers (ELISA seropositive anti-PGL-I and positive to detection the M. leprae DNA), coinciding with the most hyperendemic cluster of cases reported during the entire period, corroborating the hypothesis that this factor remains large district of stigma, making measures of impact on health education for voluntary submission of suspects. Following the 1.4% developed leprosy contacts indicating a nine times greater chance of getting sick in the positive contacts. The PCR positivity did not confer greater risk of illness for these contacts, but demonstrated the potential of transmission of subclinical same, spreading the bacillus in endemic areas. These factors incriminated in this study are of great importance in maintaining the epidemiological chain of transmission, which would impose new intervention strategies such as chemoprophylaxis of contacts. GIS with the epidemiological indicators of evaluation of morbidity and burden of disease associated with immunological and molecular tests of the population at risk has proven to be a tool that enables visibility of leprosy by health district and neighborhoods of cities allowing to improve the surveillance of this disease and serving as an important tool to support planning of health policies to eliminate leprosy as a public health problem.